ANALISIS HUBUNGAN POSTUR TUBUH TERHADAP KECEPATAN LARI SPRINT PADA SISWA DI SMPN 17 KOTA JAMBI - Julianda; Sukendro; Sugih Suhartini (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the relationship between body posture and sprint running speed among students of SMPN 17 Jambi City. Body posture is one of the biomechanical factors that may influence movement efficiency and physical performance, including sprinting ability. This study employed a quantitative approach with a descriptive correlational design and a cross-sectional method. The population consisted of 297 ninth-grade students of SMPN 17 Jambi City, while 34 students from class IX D1 were selected as samples using cluster random sampling. Body posture data were collected through postural observation and assessment, while sprint speed was measured using a sprint running test. Data were analyzed using descriptive statistics and Pearson Product Moment correlation analysis. The results showed that the average body posture score was 23.62, indicating that students generally had good posture. The average sprint time was 7.825 seconds. Correlation analysis revealed a significant relationship between body posture and sprint running speed (r = -0.489; p = 0.003). The negative correlation indicates that better body posture is associated with faster sprint performance. The coefficient of determination showed that body posture contributed 23.9% to sprint speed performance, while the remaining 76.1% was influenced by other factors. It can be concluded that body posture plays an important role in supporting sprint performance among junior high school students.